Cyber Bullying and its Influence on Academic and Social Development of University Students during Covid-19 Pandemic: A Sociological Study - Parvin, Ruma (Green University Review of Social Sciences, 2022)
This study looked into the impact of cyberbullying on university students in Bangladesh's academic and social growth. Its goal is to learn more about the impact of cyberbullying on many characteristics that affect university students.The study with the application of quantitative method incorporating the social survey and participant observation where close ended structured questionnaire with some open ended questions has been used to find out the objectives. To select the area and respondents purposive and random sampling methods were used as a sampling technique where the data were collected by using interview survey method. It was found that a major number of women students experienced cyber bullying at least once or twice through other types of media. As the online education system has started due to covid-19 pandemic cyber bullying has increased as every student are involved in media. Social media like messenger, whatsapp, viber, emo and recently being famous among young generation is tiktok mainly through instant messaging. The main conclusion is that although the existence of cyber bullying has been demonstrated, researchon cyber bullying among undergraduates is not sufficiently developed. Future research should pay special attention to this population. The outcomes of this study reveal that cyber bullying has a significant impact on university students' academic, social, and emotional development, and that it has grown in scope as a result of the covid-19 pandemic as they were more involved in online media for academic purposes as well as to pass the time while everything was shut down. Green University Review of Social Sciences Dec 2021; 7(1-2): 112-129